DRUG UTILIZATION RESEARCH: NEED OF THE HOUR - RITIKA R. KONDRA; DR. B. B. GHONGANE (International Journal of Pharma and Bio Sciences, 2013)
Drug utilization studies involves the whole process starting from the prescriptions to the dispensing of drugs, to the administering of the prescribed drugs in a patient and finally to study the after- effects of drugs. Drug Utilization Research is a highly neglected topic in India. The interest in drug utilization studies has been escalating. This concept may be extended from the moment a drug is manufactured till its final utilization or disposal. Earlier it was conducted only as a market research but now they are conducted as part of audit programs in some countries and for studying the quality of prescriptions and medications in this country. Here we discuss the understanding of drug utilization studies, its various types, and its importance in the society, the socio-cultural, medical and economic aspects of the research.